2014
DOI: 10.1021/jm501416t
|View full text |Cite
|
Sign up to set email alerts
|

Aza-acyclic Nucleoside Phosphonates Containing a Second Phosphonate Group As Inhibitors of the Human, Plasmodium falciparum and vivax 6-Oxopurine Phosphoribosyltransferases and Their Prodrugs As Antimalarial Agents

Abstract: Hypoxanthine-guanine-[xanthine] phosphoribosyltransferase (HG[X]PRT) is considered an important target for antimalarial chemotherapy as it is the only pathway for the synthesis of the purine nucleoside monophosphates required for DNA/RNA production. Thus, inhibition of this enzyme should result in cessation of replication. The aza-acyclic nucleoside phosphonates (aza-ANPs) are good inhibitors of Plasmodium falciparum HGXPRT (PfHGXPRT), with Ki values as low as 0.08 and 0.01 μM for Plasmodium vivax HGPRT (PvHGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 40 publications
1
91
0
Order By: Relevance
“…31 For Series 1, 2 and 3 the addition of a bromine atom at position 8 in the purine ring led to an increase in K i values ( Table 1 derivative was due to a rotation of the purine ring which resulted in increased interactions between the phosphonyl oxygens and active site residues (PDB codes: 4RAB and 4RAD). 39 Clearly, this has not occurred with the ANbPs and it is concluded that the decrease in inhibition constant is due to the fact that the orientation of the base with a bromine attached at position 8 resulted in a decrease in such interactions.…”
Section: Chemistrymentioning
confidence: 98%
See 1 more Smart Citation
“…31 For Series 1, 2 and 3 the addition of a bromine atom at position 8 in the purine ring led to an increase in K i values ( Table 1 derivative was due to a rotation of the purine ring which resulted in increased interactions between the phosphonyl oxygens and active site residues (PDB codes: 4RAB and 4RAD). 39 Clearly, this has not occurred with the ANbPs and it is concluded that the decrease in inhibition constant is due to the fact that the orientation of the base with a bromine attached at position 8 resulted in a decrease in such interactions.…”
Section: Chemistrymentioning
confidence: 98%
“…19 However, phosphoramidate prodrugs (Scheme 4) of aza-ANPs have been shown to possess antimalarial activity 39,40 so prodrugs of these new compounds were synthesised (Scheme 4) to evaluate their effectiveness in vitro. The results of these in vitro tests are summarized in Table 2.…”
Section: In Vitro Antimalarial Study In Erythrocyte Cell Cultures Infmentioning
confidence: 99%
“…[5][6][7][8][9] Importantly, the mode of action of the ANPs is different from the currently used drugs, so represents a new approach to developing antimalarial therapeutics. An efficient synthetic methodology to access the desired 6-oxopurine ANPs with the (1H-1,2,3-triazol-4-yl)phosphonic acid moiety has been developed and optimized.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…1) and aza-ANPs ( Fig. 1) have antimalarial [5][6][7][8][9] and/or antimycobacterial [10][11] activity. Several different chemical types of ANPs, including modified PMEA analogues, have also been studied as potent inhibitors of bacterial adenylate cyclases, namely adenylate cyclase toxin from Bordetella pertussis and edema factor from Bacillus anthracis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation